Psychosocial risk factors for coronary heart disease. Issue 3 (5th August 2013) - Glozier, Nick; Tofler, Geoffrey H; Colquhoun, David M; Bunker, Stephen J; Clarke, David M; Hare, David L; Hickie, Ian B; Tatoulis, James; Thompson, David R; Wilson, Alison; Branagan, Maree G
Summary: In 2003, the National Heart Foundation of Australia published a position statement on psychosocial risk factors and coronary heart disease (CHD). This consensus statement provides an updated review of the literature on psychosocial stressors, including chronic stressors (in particular, work stress), acute individual stressors and acute population stressors, to guide health professionals based on current evidence. It complements a separate updated statement on depression and CHD. Perceived chronic job strain and shift work are associated with a small absolute increased risk of developing CHD, but there is limited evidence regarding their effect on the prognosis of CHD. Evidence regarding a relationship between CHD and job (in)security, job satisfaction, working hours, effort–reward imbalance and job loss is inconclusive. Expert consensus is that workplace programs aimed at weight loss, exercise and other standard cardiovascular risk factors may have positive outcomes for these risk factors, but no evidence is available regarding the effect of such programs on the development of CHD. Social isolation after myocardial infarction (MI) is associated with an adverse prognosis. Expert consensus is that although measures to reduce social isolation are likely to produce positive psychosocial effects, it is unclear whether this would also improve CHD outcomes. Acute emotional stress may trigger MI or takotsubo ("stress") cardiomyopathy, but the absolute increase in transient risk from an individual stressor is low. Psychosocial stressors have an impact on CHD, but clinical significance and prevention require further study. Awareness of the potential for increased cardiovascular risk among populations exposed to natural disasters and other conditions of extreme stress may be useful for emergency services response planning. Wider public access to defibrillators should be available where large populations gather, such as sporting venues and airports, and as part of the response to natural and other disasters.